Relationship Between Body Image and Food Intake with Nutritional Status of Dancers at Goong Prada Management Surabaya - Izzah, Aqidatul (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Dance is an expression of the soul in the form of beautiful and rhythmic body movements. Dancers are an important factor in achieving the success of a dance performance. As someone who always presents themselves, appearance and posture are important for a dancer. This is related to body image which describes the way dancers view their own body shape. Body image affects food intake and results in nutritional status. This study aims to examine the relationship between body image and food intake with nutritional status in dancers at the Goong Prada Management Surabaya. This study is a correlational quantitative study using a cross sectional approach. Sampling was done by purposive sampling method totaling 42 dancers aged 13-27 years. In this study there are independent variables including body image and food intake and the dependent variable is nutritional status. Body image data collection using the BSQ-34 questionnaire and food intake using 2x 24-hour recall then calculated using Nutrisurvey. For nutritional status, body weight was measured with digital scales and height with microtoise. Data analysis used bivariate analysis with the Spearman Rank correlation test. The results showed that 74% of respondents had a positive body image, the respondents' food intake was mostly in deficit (energy intake = 88%; protein intake = 90%; carbohydrate intake = 88%; fat intake = 50%) and 88% of respondents had normal nutritional status.. The results of the analysis showed that there was no relationship between body image (p=0.935) and food intake (energy p=0.610; protein p=0.274; carbohydrates p=0.610; fat p=0.976) with the nutritional status of dancers at the Goong Prada Management in Surabaya.